2020
DOI: 10.3390/geosciences10110431
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of the Acetylene Inhibition Technique Using Time Series Analysis on Air-Dried Floodplain Soils to Quantify Denitrification Potential

Abstract: Denitrification in floodplain soils is one key process that determines the buffering capacity of riparian zones in terms of diffuse nitrate pollution. One widely used approach to measure the denitrification potential is the acetylene inhibition technique that requires fresh soil samples. We conducted experiments with air-dried soils using a time series analysis to determine the optimal rewetting period. Thus, air-dried soil samples from six different floodplain areas in Germany were rewetted for 1 to 13days to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This modification is based on the common assay for measuring denitrification enzyme activity (DEA) with the AIT developed by Smith and Tiedje (1979), that was modified by Groffman et al (1999). Comparative method trials concluded that the use of soils with high nutrient and low sand contents reduces the risk of bias (Qin et al, 2013), which justifies the applicability of the AIT in the context of this study (Kaden et al, 2020). In short, soil samples were pre-incubated for 7 days (d) to 100% water-filled pore space (WFPS).…”
Section: Potential Denitrificationmentioning
confidence: 90%
See 2 more Smart Citations
“…This modification is based on the common assay for measuring denitrification enzyme activity (DEA) with the AIT developed by Smith and Tiedje (1979), that was modified by Groffman et al (1999). Comparative method trials concluded that the use of soils with high nutrient and low sand contents reduces the risk of bias (Qin et al, 2013), which justifies the applicability of the AIT in the context of this study (Kaden et al, 2020). In short, soil samples were pre-incubated for 7 days (d) to 100% water-filled pore space (WFPS).…”
Section: Potential Denitrificationmentioning
confidence: 90%
“…This method has been proven to work when comparing soils and ecosystems (Groffman et al, 2006;Felber et al, 2012;Russell et al, 2019) and allows the soil DP to be estimated at the landscape level. Parameters leading to bias are adjusted to be as low as possible, by using the AIT modified by Kaden et al (2020), which addresses a time series analysis of rewetting as this is likely to strongly affect denitrification. This modification is based on the common assay for measuring denitrification enzyme activity (DEA) with the AIT developed by Smith and Tiedje (1979), that was modified by Groffman et al (1999).…”
Section: Potential Denitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential soil N 2 O flux was measured using a dissolved N 2 O microsensor (Unisense, Germany) [68,69]. Into 40 mL glass vials, 10 g field-moist soils and 35 mL nutrient solution containing KNO 3 and glucose (Kellogg Biological Station) [70][71][72] were added. Following the same protocol, a control for each sample was also analyzed, with 35 mL nutrient solution and no soil.…”
Section: Soil Collection Processing and Analysismentioning
confidence: 99%
“…A revetment addition invariably changes the original magnitude and pathways of the material and energy exchange, as well as affecting water transport, nutrient transport, and heat exchange. These changes contribute to bringing changes in the soil moisture [14,15], temperature [16,17], carbon and nitrogen contents [18][19][20], pH [21][22][23], and oxygen [24,25] at RRIs among different revetments. These variables, in turn, influence soil nitrification and denitrification at RRIs.…”
Section: Introductionmentioning
confidence: 99%